Clicks and Conversations: Exploring the Factors Influencing Frequency of Ilokano Language Usage - Lachica, John Mark (EDULANGUE, 2024)
Investigating the factors influencing the frequency of language usage in a community is crucial for understanding the vitality of its native language. This qualitative study investigated the health of the Ilokano language through an exploration of the factors that affect language use among selected Ilokano speakers in the municipality of Agoo, La Union. A written/mailed interview was used to capture relevant data for exploring this exploration. The findings of the study revealed a concerning trend, revealing two emerging factors significantly influencing language use: 1) generational shifts and 2) technological advances. Recognizing and addressing the factors contributing to the decline of Ilokano in Agoo is essential for fostering linguistic diversity and cultural richness and maintaining a vibrant local identity. This deficiency in research on language vitality is particularly concerning given the intricate interplay of sociocultural, economic, and technological factors that shape the linguistic landscape of diverse communities. While there are challenges due to generational shifts and technological advances, ongoing enhancement efforts offer hope for the future of Ilokano. Despite the challenges, the future of Ilokano is not predetermined. By acknowledging its importance, supporting enhancement efforts, and embracing technological opportunities, the Ilokano community can ensure the language continues to thrive for generations to come.